Challenges in Teacher Leadership: Workload, Time Allocation, and Self-Esteem - Zydziunaite, Vilma; Kontrimiene, Simona; Ponomarenko, Tetiana; Kaminskiene, Lina (European journal of contemporary education, 2020)
In research on teacher leadership, teacher workload, teaching time allocation, and teacher self-esteem in teaching and at school are neither studied as challenges or influencing factors nor are they seen as related to leadership at all. In educational research the mentioned factors are mostly studied in relation to teaching effectiveness or quality. The present study is aimed at identifying the relationship between teacher workload, time allocation, self-esteem, and leadership at school. The study involved 418 subjects, primary school, pre-school, and vocational teachers. Results suggest no significant differences among teachers in terms of aggregate study variables by the type of school or teachers' position at school, yet differences emerged among teachers with different workloads in two composite variables, school activity and school stress as teachers with less than half a day workload are statistically significantly less active at school and experience less stress than full-time teachers; also, there is a significant link between teacher workload and time allocated to a number of activities as well as stress, and the same two determinants of teacher self-esteem both in teaching and at school are the level of activity in school and stress. The other variables important in the formation of teacher self-esteem differ, although both types of self-esteem are interrelated as the level of one is predictive of the level of the other. These findings accentuate that workload, time allocation, and self-esteem are important challenges in teacher leadership. The relationship between teacher workload, time allocation, self-esteem, and leadership needs to be defined and managed at the institutional and individual levels to avoid potentially undesirable effects and counterproductive teaching and learning behaviors.